(untitled) (Journal of the College of Education for Women, 2019)
Iraq has confronted a huge political transformations after 2003 which resembled and presented rapid changes from totalitarian regime into democracy’s system , this phenomenon has become a feature embodied in a new political system, specifically is being a price for previous deprivation and despotism .So that, the nature of political work has been changed as a result of practicing new democratic values ,but the real challenges appeared by depending on the conformity and political compromise in dealing with all of crises and problems in the political life .The future of political work in this nascent democracy could be prepared according to fulfillment an active doings values stretched on national unity and forgiveness from one side ,to reach into the reconciliation and solving all pending problems by national settlement ( Historic settlement ) as proclaimed to be compatibility with the values of justice and good governing according to the state of law at another side , by making political democratic process beyond of compromise or disputing wills and eliminating of so - called the quota approach of its components which led to instability within Iraq’s political society as much as increasing of popular demands which claimed overhaul in all fields of political life recently .